ANALISIS KEBIJAKAN MANAJEMEN BERBASIS SEKOLAH DALAM PENINGKATAN MUTU PENDIDIKAN - Adriani Adriani; Ervina Jamaluddin; Nur Syamsu Rida; Andri Yogi Pramadana (Institusi Agama Islam Negeri (IAIN) Bone, 2020)
Public expectations for quality education are in line with the demands of the business community to obtain a quality workforce. Thus, the organization of education must be able to respond and accommodate these expectations and demands in the decision making process to improve the quality of education. This study aims to describe and analyze school-based management in improving the quality of education, as well as the obstacles faced by schools in implementing school-based management. The research method used in this study is a descriptive method with a qualitative approach. Data collection used through literature study.